Bicuspid aortic valve area in normal heart. Issue 3 (20th February 2020) - Katz, Moshe; Mazin, Israel; Kuperstein, Rafael; Beigel, Roy; Vaturi, Ori; Feinberg, Micha S; Raanani, Ehud; Ben Zekry, Sagit
Abstract: Introduction: Bicuspid aortic valve (BAV) is a common congenital valve abnormality. There are no data in the literature regarding the range of aortic valve area (AVA) in normal functioning BAV. We aimed to evaluate the normal range of BAV area and to compare it to subjects with tricuspid aortic valve (TAV). Methods: Bicuspid aortic valve subjects were identified from Sheba medical center echocardiographic database and were compared with TAV subjects. Inclusion criteria were normal tissue leaflets appearance and normal functioning valve in the presence of normal echocardiogram. Echocardiographic data, patients hemodynamics, and size were collected. AVA was measured with both planimetry and the continuity equation. Results: Fifty BAV and 50 control subjects were studied (37 men, age 40 ± 13 years). All studies were performed with normal hemodynamics. Fusion between the coronary leaflets was the most common morphology (82%), followed by fusion between the right coronary leaflet with the noncoronary leaflet (18%). The left ventricular outflow tract (LVOT) diameter in BAV group was significantly larger (2.3 ± 0.3 cm vs 2.1 ± 0.2; P < .001). The BAV group presented with a larger AVA planimetry (3.8 ± 0.9 vs 3.3 ± 0.6; P < .001). However, measuring AVA using continuity equation has shown no differences between groups. If using the principles of coefficient of contraction, it seems that measuring AVA by planimetry overestimates the real anatomic AVA. Conclusion: This data provide normal values for echocardiographically determined AVA in BAV subjects. This population was characterized by large LVOT diameter and large AVA. The larger AVA measured with the planimetry emphasizes the limitation of this method in BAV population.